AJARAN BHATARA KUMARA DALAM TUTUR KUMARA TATWA DAN PENGARUH TERHADAP KEHIDUPAN MANUSIA - I Wayan Artayasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Hindus considered Bhatara Kumara in Bali as a protector or guardian deity fornewborn children. Offering and worshiping Bhatara Kumara is very important to do every dayto protect or give children gifts. However, in Tutur Kumara Tatwa, Bhatara Kumara teachingsare not only for children but for all people.The teachings conveyed are a form of self-control in this life. The teaching or educationin Tutur Kumara Tatwa certainly has implications for human life, especially in Bali. Children'seducation is essential to do from an early age to develop good character. Good character isnot only for children but also applies to all human beings. According to Tutur Kumara Tatwa,character education from Bhatara Siwa to Bhatara Kumara originated from a field whereBhatara Kumara was grazing called Argakuruksana. Bhatara Kumara felt like life in solitude.During his life as a shepherd, he had experienced many ups and downs. It is what can belearned as teaching or values in life that can affect human life.Bhatara Kumara was blessed or awarded by Bhatara Shiva to stay young, achievingeternal happiness. Bhatara Kumara is represented as the god of a baby. It means that babiesshould have received character education from their parents. Bhatara Kumara's role in humanlife, especially for Bali's Hindu community, is seen as the God of children from birth to TelungOton's age (630 days). Bhatara Kumara is placed in Pelangkiran and is believed to be thechild's protector or guardian.